Representasi Peran Ayah Sebagai Orang Tua Tunggal dalam Film Pendek “Mana Janji Ayah” (Semiotika Rolland Barthes) - Ani Gusliyani; April Laksana; Putri Handayani; Achmad Nashrudin; Meiby Zulfikar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to determine the representation of the father's role as a single parent in the short film "Mana Janji Ayah." The study used a qualitative method with Roland Barthes's semiotic analysis focusing on three layers of meaning: denotation, connotation, and myth. The analysis was conducted on scenes depicting the father's role, including as protector, patient, breadwinner, caretaker, and bringer of happiness to children. The results show that the representation of fathers is not limited to financial functions but also encompasses emotional and moral roles, such as affection, responsibility, and sacrifice in raising children. The film depicts a single father who works as a bajaj driver to support his children after the death of his wife, despite often facing economic constraints and environmental stigma. This representation is conveyed through visual and audio cues that reinforce the message of a father's struggle and sincerity. This study confirms that film can be a medium that reflects social reality, particularly the complexity of the role of single fathers, which is often overlooked in society.